The Cosmed K5 - invalid for measuring oxygen consumption in the cold - Docter, H.; de Koning, J. J.; FACSM; Noordhof, A. (Book of Abstracts. 4th Nordic Winter Sports Conference "Performance in snow sports: Translating science into practice" 3rd-4th October, 2022, Mid Sweden University, Campus Östersund, Sweden, 2022)
Mode-specific measurements of oxygen uptake performed in the field are helpful to understand and optimize athletic performance. In winter sports, field measurements are challenging due to the low ambient temperatures, in which devices are not validated.